(untitled) (Research, Society and Development, 2021)
Objective: To investigate the association between the change in the estimated Glomerular Filtration Rate in elderly people with the use of Potentially Inappropriate Medicines for the elderly and polypharmacy. Methodology: Cross-sectional and analytical study based on data from 1216 elderly users of the Public Health System who had estimated Glomerular Filtration Rate exams, the same being considered altered when <60mL / min / 1.73m2. Descriptive analyzes, univariate analysis “chi-square test (χ2) or Fisher’s exact test” were performed and variables with p <0.2 were included in the multivariate logistic regression analysis. Results: Of the total number of patients, 541 (44.5%) had altered estimated Glomerular Filtration Rate, 943 (77.5%) used polypharmacy and 588 (48.3%) used Potentially Inappropriate Medicines for the elderly. Multivariate analysis showed that men over 80 years of age are more likely to have their estimated Glomerular Filtration Rate altered and that the practice of polypharmacy increased the chances of alterations in this parameter by 1.62 (p = 0.004; OR: 1.62; CI: 1, 67 - 2.24). In addition, the use of Potentially Inappropriate Medicines increased the chances of having the estimated Glomerular Filtration Rate altered by 1.49 times (p = 0.003 OR: 1.49; CI: 1.15 - 1.93). Conclusion: This study showed a high frequency of using of polypharmacy and Potentially Inappropriate Medicines in the elderly and this population was shown to have a greater chance of impairing renal functions. Thus, this finding brings an alert to public health and points to the necessity to invest in a therapeutic approach as a focus on the safety of elderly patients.